PENTINGNYA PENANAMAN BUDI PEKERTI SEJAK USIA DINI - Amanudin Amanudin; Lollong Manting; M. Zhafri; Ian Permana Wahyu; Lukman Hakim (LPPM Universitas Pamulang, 2020)
Children are the new generation who will continue the ideals of the struggle of the nation and human resources for national development. In addition, children are the nation's assets where the future of the nation and state rests on their shoulders. For this reason, children need to be directed, guided, instilled in their overall values in the form of character and given knowledge so that they have competitiveness with the abilities and desires they have on the basis of noble character. This is because every child has a character that can be directed and potential that can be developed. The potential or ability of a true child has existed since he was born on this earth, but will grow and develop with the guidance in learning. Therefore, learning must be a child's priority to be considered. Learning is an effort to find new things, which have not been known before. The government has provided educational facilities to provide a place for Indonesian children to learn. Schools are formal institutions whose job is to organize education where children as the next generation of the nation will learn to gain knowledge. However, learning is not focused on formal education in schools, but learning can be done anywhere, in informal institutions, nature, playing environment and so on, as well as in TPQ or TPA as an informal educational institution that organizes education and teaching in the field of religion. Through the learning process children will be able to develop the potential that exists in their respective individuals. Learning is also very important for children so they can adapt and solve problems both related to friends and the environment, as well as problems that will arise in their lives as adults. It is hoped that Indonesian children can grow and develop with good education and have a personality in the form of good character so that they can work for Religion, and the Nation. The importance of instilling the value of character is the background of the Faculty of Teacher Training and Education, Pamulang University Economic Education Study Program to carry out community service in one of the informal educational institutions namely TPQ and TPA Almuhajirin, with the title